Ancient Schwannoma Presenting as Sciatica Mimicker: A Case Report - S Vijaya Anand; Krishnakumar Ramachandran; HD Bharath; Ranjima Abraham (Journal of Orthopedics and Joint Surgery)
Sciatica is the pain that radiates from the lower back or buttock to the posterior thigh, calf, and towards the foot. The most common cause of sciatica is intervertebral disc prolapse or degenerative spinal conditions. A few rare conditions also cause sciatica-like symptoms, termed sciatica mimicker. A case report of a 26-year-old male with back pain and radiating pain to both lower limbs. On examination, he had a positive straight leg raising test (SLR). On Magnetic resonance imaging, he had an intradural extramedullary tumor (IDEM) at the L1 level. He underwent posterior decompression and surgical resection of the tumor. Histopathological examination (HPE) consistent with Schwannoma. Lumbar schwannoma is a benign slow-growing intradural extramedullary tumor presented as a sciatica mimicker. After surgery, the patient becomes symptomatically better.